2018
DOI: 10.1590/2177-6709.23.5.065-074.oar
|View full text |Cite
|
Sign up to set email alerts
|

Perception of attractiveness of missing maxillary lateral incisors replaced by canines

Abstract: Objective: The aim of this study was to evaluate the degree of perception of attractiveness of the smile among dentists, dental students, and lay persons in cases of agenesis of the maxillary lateral incisors replaced by canines for space closure. Methods: A smiling front view extraoral photograph of a 20-year-old woman was digitally altered simulating agenesis and its treatment, by means of: repositioning, reshaping or bleaching the canine, and gingival contour. A questionnaire was distributed to individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 22 publications
0
16
0
2
Order By: Relevance
“…Therefore, perceptions of dental esthetics can vary between dental professionals and laypersons. In fact, Nonprofessional observers considered a simple dental reshaping of the canine to be attractive, while the dental professionals considered gingival and crown reshaping to be more esthetic [15][16][17]. Nevertheless, this option can have some inconveniences such as the lack of development of canine guidance, flattening of the facial profile with an increase in the nasolabial angle and a possible predisposition to a Class III relationship [18].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, perceptions of dental esthetics can vary between dental professionals and laypersons. In fact, Nonprofessional observers considered a simple dental reshaping of the canine to be attractive, while the dental professionals considered gingival and crown reshaping to be more esthetic [15][16][17]. Nevertheless, this option can have some inconveniences such as the lack of development of canine guidance, flattening of the facial profile with an increase in the nasolabial angle and a possible predisposition to a Class III relationship [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, for some patients with CMLI, the final esthetic outcome may be acceptable by mere orthodontic space closure and canine reshaping, without any remodeling of the periodontal profile and restorations at all. It has been reported that lay people are less critical than dental professionals in the evaluation of dental esthetics, 27,28 and that mere space closure achieves a higher esthetic score than any prosthetic replacement for CMLIs. 29,30 Fig .…”
Section: Outcome Evaluation Of Dental Estheticsmentioning
confidence: 99%
“…One of the facial expressions that arises more interest in people and composes the beauty of it is the smile. [1][2][3] Therefore, studies have been conducted in order to reach a desired set of common characteristics for an optimal aesthetic smile. This goal is without successful perspective, since culture and ethnicity, values on what is beautiful and ugly or right and wrong vary on different continents, being illusory the idea of reaching a common denominator on this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…5 Teeth and gum exposure are important factors regarding the assessment of the aesthetic smile, and their perception varies in different societies. 1…”
Section: Introductionmentioning
confidence: 99%